Mathematical activities : A resource book for teachers - Bolt, Brian (Cambridge : New York : Cambridge University Press, 1987)
This book contains more than 150 games, puzzles and investigations designed to motivate everyone interested in mathematics. Many of the activities encourage creative thinking and practical work. The book provides a resource of ideas for all those concerned with mathematical education.
Includes bibliography references.
Keywords: Mathematical recreations; Puzzles